2020
DOI: 10.1096/fj.202000511rr
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoma‐derived growth factor participates in concanavalin A‐induced hepatitis

Abstract: Hepatitis is an important health problem worldwide. Novel molecular targets are in demand for detection and management of hepatitis. Hepatoma-derived growth factor (HDGF) has been delineated to participate in hepatic fibrosis and liver carcinogenesis. However, the relationship between hepatitis and HDGF remains unclear. This study aimed to elucidate the role of HDGF during hepatitis using concanavalin A (ConA)-induced hepatitis model. In cultured hepatocytes, ConA treatment-elicited 2 | WANG et Al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…To analyze the clinical relevance of necroptotic mediators in liver transplantation and end-stage liver diseases, immunohistochemistry was performed on consecutive liver slices using validated RIPK3 18 , 19 and phosphorylated mixed lineage kinase domain-like (pMLKL) 20 , 21 antibodies. A cholangiocyte-specific cytokeratin-19 antibody was applied to localize bile ducts.…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the clinical relevance of necroptotic mediators in liver transplantation and end-stage liver diseases, immunohistochemistry was performed on consecutive liver slices using validated RIPK3 18 , 19 and phosphorylated mixed lineage kinase domain-like (pMLKL) 20 , 21 antibodies. A cholangiocyte-specific cytokeratin-19 antibody was applied to localize bile ducts.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the activation of pMLKL is involved in rat hepatic IRI, rat liver biopsies were collected after 22 hours of cold storage and 24 hours of reperfusion or sham operation ( Figure 1A ), followed by immunohistochemistry staining of pMLKL using a validated antibody ( 27 , 40 , 41 ). Compared to sham-operated rats, a significant increase of serum ALT (1153.0 (441.5-1652.0) vs 10.0 (10.0-17.5), p =0.029) and AST (1294.0 (654.5-1497.0) vs 66.5 (47.0-94.0), p =0.029) levels was observed in rats after LT ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that HDGF stimulates cell proliferation in fibroblasts, endothelial cells, and hepatoma cells [ 10 ] as well as mediates inflammation [ 33 ]. Consistent with these findings, our study showed that treatment with rHDGF ab could decreased the proliferation of microglia and astrocytes as well as reduced the levels of pro-inflammatory factors induced by SAH (Figs.…”
Section: Discussionmentioning
confidence: 99%